Three little words : a memoir - Rhodes-Courter, Ashley, 1985- (New York : Atheneum, 2008)
Ashley spent nine years in foster care after being taken away from her mother. She endured many caseworkers, moving from school to school and manipulative, humiliating and abusive treatment from one foster family. See how she survives and eventually thrives against the odds.
Keywords: Rhodes-Courter, Ashley, -- 1985-; Adopted children -- United States -- Biography; Foster children -- United States -- Biography; Foster home care -- United States